Negotiating Inclusive Islamic Da‘wah within Multicultural Contexts: Muslim Minority Experiences in Bali - Muhammad Ridwan; Muhamad Tohayudin (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
Islamic da’wah in multicultural societies faces growing complexity, particularly when Islam is positioned as a minority faith within a dominant cultural tradition. In Bali, where Hindu values strongly shape social life, da’wah encounters distinctive social, cultural, and symbolic challenges that demand adaptive and inclusive approaches. This study aims to examine how Islamic da’wah is practiced by Muslim minority communities in Bali within a multicultural social environment. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis to capture the lived da’wah practices in context. The findings show that da’wah in Bali is not primarily conducted through confrontational verbal preaching or symbolic expansion. First, da’wah bil-ḥal emerges as the dominant strategy, emphasizing moral exemplarity, social contribution, and everyday interaction. Second, internal community strengthening is prioritized as a means of preserving religious identity and resilience amid minority conditions. Third, interreligious relations are managed through informal social engagement and cultural sensitivity rather than formal dialogue alone. These strategies demonstrate that da’wah functions as a social practice embedded in daily life and intercultural communication. This study contributes empirically and theoretically to inclusive da’wah and minority Islam studies, and recommends comparative and mixed-methods research to broaden the understanding of da’wah in multicultural minority contexts.